Respiratory system toxicity induced by immune checkpoint inhibitors: A real-world study based on the FDA adverse event reporting system database - Chanjuan Cui; Lei Deng; Wenqing Wang; Xiayang Ren; Yanfeng Wang; Wei Cui (Frontiers in Oncology, 2022)
BackgroundImmune checkpoint inhibitors (ICIs), the treatment of multiple cancer types, can be associated with respiratory system adverse events (AEs). The aim of this study is to quantify the association of respiratory system AEs and ICIs and to characterize the profiles of ICI-related respiratory system complications from Food and Drug Administration Adverse Event Reporting System (FAERS) data.MethodsThe disproportionality of respiratory system AE-related ICIs based on FAERS data from January 2014 to September 2021 was analyzed using the reporting odds ratio (ROR) and information component (IC) as measures of potential risk increase.ResultsA total of 38,415,849 records were involved; among these, 36,923 records related to respiratory system AEs after ICI treatment were identified. In the first 3 months, the cumulative proportion of respiratory system AEs was 75.40%. Men had a slightly higher reporting frequency than that of women (ROR = 1.74, 95% CI: 1.70–1.78). Death cases had a slightly higher reporting frequency in ICI-associated respiratory system AEs than that of other drug-associated respiratory system AEs (ROR = 1.40, 95% CI: 1.38–1.41). Anti-programmed cell death 1 (PD-1) drugs and anti-programmed cell death ligand 1 (PD-L1) drugs were significantly associated with respiratory system toxicities. However, anti-cytotoxic T lymphocyte-associated protein 4 (CTLA-4) drugs did not demonstrate an association with respiratory system toxicities. Interstitial lung disease and pneumonitis were found to be significantly associated with all eight types of ICIs. In addition, 7 in 10 class-specific respiratory system AEs (lower respiratory tract disorders, pleural disorders, pulmonary vascular disorders, respiratory disorders not elsewhere classified (NEC), respiratory tract infections, respiratory tract neoplasms, and thoracic disorders) were associated with ICIs. The signal values of IC025 were from 0.08 to 2.66.ConclusionsOverall, this study showed a high reporting frequency of respiratory system toxicities caused by ICIs. Early recognition and management of ICI-related respiratory system AEs are of vital importance in practice. Maximizing the benefit while reducing potential respiratory system toxicities of ICIs should become a priority.